2017
DOI: 10.1039/c7ra11437k
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous enhancements in the mechanical, thermal stability, and flame retardant properties of poly(1,4-butylene terephthalate) nanocomposites with a novel phosphorus–nitrogen-containing polyhedral oligomeric silsesquioxane

Abstract: A novel functionalized POSS greatly reinforced the mechanical, thermal stability, and flame retardant properties of PBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The elemental composition of EP-0 was comparable in exterior and interior char layer, while in the case of EP-3, the P and Si elements in the exterior layer are much higher than those in the interior layer, which might be attributed to the migration of phosphorus and silicon during combustion. 43 Besides, it can be observed that the oxygen content increased, and carbon content decreased on the exterior char layer of EP-3, compared to that of EP-0. The reason is that the exterior char was highly oxidized under the rich oxygen condition and a number of Si O 2 and P O structures were retained in the char.…”
Section: Gaseous and Condensed Phases Analysismentioning
confidence: 91%
“…The elemental composition of EP-0 was comparable in exterior and interior char layer, while in the case of EP-3, the P and Si elements in the exterior layer are much higher than those in the interior layer, which might be attributed to the migration of phosphorus and silicon during combustion. 43 Besides, it can be observed that the oxygen content increased, and carbon content decreased on the exterior char layer of EP-3, compared to that of EP-0. The reason is that the exterior char was highly oxidized under the rich oxygen condition and a number of Si O 2 and P O structures were retained in the char.…”
Section: Gaseous and Condensed Phases Analysismentioning
confidence: 91%
“…Though polymers are used widely in both daily life and industry, the thermal stability, mechanical properties, and electrical properties of polymers still need to be improved. SSQs, especially POSS, are attractive hybrid nanomaterials that can provide polymers with superior thermal properties . SSQs with a rigid Si–O–Si framework show excellent thermal properties and SSQ‐containing polymers exhibit good thermal properties even after a physical blending process .…”
Section: Advanced Applicationsmentioning
confidence: 99%
“…Nevertheless, PBT resins without flame retarded modification are easily ignitable either by an electric spark or short circuitry within the electrical network which could lead to serious melt-dripping, rapid flame propagation and large production of smoke in an untenable fire condition. With attempts being made to fire-proof PBT, only few nanoadditives, e.g., nano-clay [ 3 , 4 , 5 ], graphene [ 6 ] and polyhedral oligomeric silsesquioxane (POSS) [ 7 ], have been explored to improve the flame retardancy of PBT, as well as other properties. Camino et al [ 3 ] reported an organoclay which was prepared by the ion exchange of original alkaline cations with dimethyl hydrogenated tallow benzyl quaternary ammonium chloride.…”
Section: Introductionmentioning
confidence: 99%
“…The peak heat release rate and smoke production rate values of MnCo 2 O 4 –GNS/PBT composites were decreased by 39.4 and 35.7%, respectively. In our previous study [ 7 ], functionalized POSS with phosphorus-containing agent showed significant fire retarded effect in PBT. Apart from the reported flame retardant additives, aluminum phosphinate and aluminum hypophosphite with similar molecular structure and relatively high oxidation state of phosphorus atom have proven to be very effective flame retardants for PBT, due to a combination of gas-phase flame inhibition effect and barrier effect of char layers in the condensed phase [ 4 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%